Six- and Twelve-Month Outcomes among Homeless Youth Accessing Therapy and Case Management Services through an Urban Drop-in Center - Slesnick, Natasha (Blackwell Science Inc, 2008)
RESEARCH OBJECTIVE: To evaluate the impact of case management and individual therapy offered through a drop-in center for homeless youth on substance use, mental health, housing, education, employment, and medical care utilization. STUDY POPULATION: All youth (n=172) between the ages of 14–24 who accessed treatment services through an urban, southwestern drop-in center were included. DATA SOURCE: Semistructured and self-report questionnaires were administered to youth between October 2002 and April 2005. STUDY DESIGN: A repeated measures design was utilized. Youth were assessed at baseline, 6 months, and 12 months postbaseline. Hierarchical linear modeling was used to test the hypotheses. PRINCIPAL FINDINGS: Statistically significant improvements were found in substance abuse, mental health, and percent days housed up to 12 months postbaseline. Decreased alcohol and drug use was associated with an increase in housing. However, most youth did not acquire permanent housing, and education, employment, and medical service utilization did not significantly change over time. CONCLUSIONS: While treatment offered through drop-in centers for homeless youth can positively impact homeless youth, policy, funding, and service provision need greater focus, collaboration, and support if youth homelessness is to be successfully addressed.